Stability indicating thin-layer chromatographic method for estimation of antidiabetic drug Remogliflozin etabonate - Dimal A. Shah; Ishita I. Gondalia; Vandana B. Patel; Ashok Mahajan; Usmangani Chhalotiya; Dhruti C. Nagda (SpringerOpen, 2021)
Abstract Background A sensitive, precise, and stability-indicating high-performance thin-layer chromatographic (HPTLC) method has been developed for the analysis of Remogliflozin etabonate in tablet formulation. HPTLC plates precoated with silica gel 60 F254 were used as the stationary phase; methanol: ethyl acetate: toluene: NH3 (2:4:4:0.1, v/v/v) was used as mobile phase, and densitometry was used for the quantitative estimation of the drug. The proposed method was validated with respect to linearity, accuracy, precision, and robustness and applied for the estimation of drug in tablet dosage form. Results The R f value of Remogliflozin etabonate was observed to be 0.61. The densitometric estimation was performed in reflectance mode at 229 nm. The method was found to be linear in the range of 500-8000 ng/band for Remogliflozin etabonate. The possible degradation pathway was estimated by performing forced degradation studies. The degradant peaks were well resolved from the drug peak with acceptable resolution in their R f value. Conclusion An accurate and precise high-performance thin-layer chromatographic method has been developed for the quantification of Remogliflozin etabonate in tablets. Forced degradation studies were performed, and drug was found to be highly susceptible to acid, base hydrolysis, and oxidative stress degradation and gets converted into active drug Remogliflozin. Both Remogliflozin etabonate and Remogliflozin bands were well resolved. The method was applied for the analysis of drug in tablet formulation, and it can be used for routine quality control analysis, as well as for the analysis of stability samples.